Effects of cyclones on tropical rain forest structure and dynamics - Wan Mohammad, Syarifah Kamariah (2015)
Spatial patterns of forest trees, stand level effects of cyclones, and factors affecting mortality and growth of individual trees were investigated in 20 experimental plots (0.5 ha) in North Queensland tropical rain forests, Australia. Cyclone disturbance has been recorded in individual plots for 20 times since establishment in 1971. Spatial point patterns of trees were mapped, and pair correlation and mark correlation function were used to investigate relationships between the trees. Effects of cyclones on stand level properties of the forests (total basal area, stem densities, stem size inequality, species diversity, recruitment, mortality) were estimated using generalised additive modelling. Factors affecting individual tree mortality and growth were analysed in generalised mixed effects modelling. The spatial pattern analysis showed minor changes of tree density and tree death in the forest spatial patterns following cyclones. The models revealed that the forest properties were changed significantly. Cyclones decreasing total basal area and increased tree mortality rates and number of abundant species. Higher mortality rates are likely influenced by individual tree characteristics of low wood density, negative growth rates and belonging to particular sets of families. Factors that increase growth rates are include higher crowding effects of tree density, cyclone occurrence, crowding effects by smaller trees, and trees of some families. Slower growth rates are likely influenced by higher wood density, higher surrounding basal area of competing trees and in certain families. From this research, evidence has found for cyclones to be a factor increasing stand level mortality rates but not individual tree mortality. The dynamics from individual trees in mortality and growth, forest spatial patterns and stand level properties has characterised the tropical rain forests of North Queensland in facing frequent cyclone disturbances.